The demand of car rentals : a microeconometric approach with count models and survey data - Menezes, António Gomes de (2019)
The purpose of this study is to analyze the demand side of the tourist market in a small island economy, the Autonomous Region of the Azores, a Portuguese region experienced a rapid growth in the tourism sector in the last decade. Azorean islands are, normally, a “fly-anddrive” destination given the high frequency of car rentals by the tourists. It is well known that the excessive use of cars can lead to negative externalities such as pollution and the degradation of roads. Considering the growing number of tourist in the Azores and ecological fragility that is typical for small islands, it is crucially important to investigate the extent of these negative externalities. This phenomenon is very important in terms of policy-making on the management of tourism in small island economies as well as in the global environmental context from the perspectives of effective "eco-taxes", used as instruments for internalizing negative externalities and enhancing environmental protection. To this end, the demand function of car rentals is analyzed with the use of the family of count models and the unique micro-level survey data, conducted on a large number of tourists visited the region. Based on the price elasticity of demand for care rentals, we then suggest desired tax rates for internalizing the congestion costs.